2020
DOI: 10.1007/s42729-020-00182-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Small-Scale Mechanized Logging Equipment on Soil Compaction in Forests

Abstract: The present study focuses on assessing the effects of different numbers of skidders on soil compaction. To assess the skidding effects, four-wheeled small-scale logging equipment attached to an ATV (Automated Transfer Vehicle) was used. Skidding operations were carried out on undistributed forest corridor (20 × 3 m).To measure soil compaction, 11 measurement lines were used, spaced at 2-m intervals. A total of 33 measurement points were used to measure soil compaction. Soil compaction values were measured for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Different land use types have different water yield. Varol T et al [39] evaluated the impact of different quantity of material collectors on soil compaction, which may further affect the supply of water yield service in the region. Our study found that the total amount of runoff and runoff per unit area of land use types in Wei River basin were different (Table 3).…”
Section: Analysis Of Influencing Factors Of Water Yield Service In Wementioning
confidence: 99%
“…Different land use types have different water yield. Varol T et al [39] evaluated the impact of different quantity of material collectors on soil compaction, which may further affect the supply of water yield service in the region. Our study found that the total amount of runoff and runoff per unit area of land use types in Wei River basin were different (Table 3).…”
Section: Analysis Of Influencing Factors Of Water Yield Service In Wementioning
confidence: 99%
“…In addition, the increase in BD resulting from compaction was found to be significantly different after 12 to 16 machine trips than after 3-6 trips [31]. However, up to 60 trips of the machine, the degree of pressure was significantly different from each other, but there was no significant difference between 60, 80, 100, and 120 [11]. In addition, in previous studies it has been reported that the correlation observed between traffic intensity and BD can be expressed using a logarithmic model [32].…”
Section: Introductionmentioning
confidence: 78%
“…Soil bulk density (BD) is an indicator that defines compaction [11]. Soil compaction diminishes porosity and pore continuity, which results in increased BD [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, some watersaving measures should be considered for vegetation restoration, such as precipitation collection with fish-scale pits and gravel mulching (Zheng et al 2019). Furthermore, soil compaction caused by machines is one common problem (Varol et al 2020), which may also affect the soil moisture status. That is what we should pay attention in the near future.…”
Section: The Relationship Between Soil Texture and Moisturementioning
confidence: 99%